The like economy: Social buttons and the data-intensive web - Gerlitz, Carolin; Helmond, Anne (New media & society, 2013)
The paper examines Facebook’s ambition to extend into the entire web by focusing on social buttons and developing a medium-specific platform critique. It contextualises the rise of buttons and counters as metrics for user engagement and links them to different web economies. Facebook’s Like buttons enable multiple data flows between various actors, contributing to a simultaneous de- and re-centralisation of the web. They allow the instant transformation of user engagement into numbers on button counters, which can be traded and multiplied but also function as tracking devices. The increasing presence of buttons and associated social plugins on the web creates new forms of connectivity between websites, introducing an alternative fabric of the web. Contrary to Facebook’s claim to promote a more social experience of the web, this paper explores the implementation and technical infrastructure of such buttons to conceptualise them as part of a so-called ‘Like economy’.